Electrophoretic deposition of biomimetic zinc substituted hydroxyapatite coatings with chitosan and carbon nanotubes on titanium. Issue 7 (August 2015) - Zhong, Zhenyu; Qin, Jinli; Ma, Jun
Abstract: In this study, a biomimetic method was used to prepare hydroxyapatite (HAP) and zinc substituted HAP (ZnHAP) nanoparticles, in which silk fibroin was used as template. The morphology of HAP is rod-like, while ZnHAP changes to wrinkled sheets. HAP and ZnHAP nanoparticles were used to coat titanium by EPD with additional chitosan and multiwalled carbon nanotubes. Phase composition, morphology and structure were studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared and Raman spectroscopy. The results showed that the composite coatings containing HAP and ZnHAP had homogeneous morphology and good apatite formation ability. The ZnHAP composite coating possessed class 5B adhesive strength using tape test. Furthermore, the ZnHAP composite coating had better corrosion resistance compared to the HAP composite coatings.